Skeletal and dental components of Class II correction with the bionator and removable headgear splint appliances - Martins, Renato Parsekian [UNESP]; da Rosa Martins, Joel Claudio; Martins, Lidia Parsekian [UNESP]; Buschang, Peter H. (Mosby-elsevier, 2008)
The purpose of this study was to differentiate the dentoalveolar and skeletal effects to better understand orthodontic treatment. We evaluated the treatment changes associated with the bionator and the removable headgear splint (RHS). Methods: The sample comprised 51 consecutively treated Class II patients from 1 office who had all been successfully treated with either a bionator (n = 17) or an RHS appliance (n = 17). Class II patients waiting to start treatment later served as controls (n = 17). A modified version of the Johnston pitchfork analysis was used to quantify the dentoalveolar and skeletal contributions to the anteroposterior correction at the levels of the molars and the incisors. Results: Both appliances significantly improved anteroposterior molar relationships (2.15 mm for the bionator, 2.27 mm for the RHS), primarily by dentoalveolar modifications (1.49 and 2.36 mm for the bionator and the RHS, respectively), with greater maxillary molar distalization in the RHS group. Overjet relationships also improved significantly compared with the controls (3.11 and 2.12 mm for the bionator and the RHS, respectively), due primarily to retroclination of the maxillary incisors (2.2 and 2.38 mm for the bionator and the RHS, respectively). The differences between overall corrections and dentoalveolar modifications for both molar and overjet relationships were explained by skeletal responses, with the bionator group showing significantly greater anterior mandibular displacement than the RHS group. Conclusions: The bionator and the RHS effectively corrected the molar relationships and overjets of Class II patients primarily by dentoalveolar changes. (Am J Orthod Dentofacial Orthop 2008; 134: 732-41)